A composite coating for a face of a shield cutter

CN118048626BActive Publication Date: 2026-10-27UNIV OF JINAN
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410099167.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2026-10-27
Estimated Expiration
2044-01-24

AI Technical Summary

Technical Problem

现在多是采用设置涂层的方式来提高其耐磨程度,但是现阶段所采用涂层的耐磨性和耐腐蚀性仍有待提高

Benefits of technology

[0015]1.本申请根据激光熔覆的优点,采用WC、TiC以及镍铬合金能够得到硬度和耐磨性符合要求的盾构滚刀表面复合涂层。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of composite coatings of shield cutter working surface, comprising the following mass parts of raw materials: WC: 10-25 parts;TiC: 5-20 parts;Nickel-chromium alloy: 60-80 parts;The composite coating is obtained by the above-mentioned raw materials by laser cladding method.This application can obtain the composite coating of shield cutter surface according to the advantages of laser cladding, WC, TiC and nickel-chromium alloy, which meets the requirements of hardness and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a composite coating for the cutterhead surface of a tunnel boring machine. Background Technology

[0002] The cutterhead is the "teeth" of a tunnel boring machine (TBM) for tunnel excavation, primarily responsible for breaking hard rock. However, due to prolonged contact with rock and the influence of the damp underground environment, the cutterhead is the most wear-prone component of the TBM. Because TBMs are large machines, cutterhead replacement is exceptionally difficult. Cutterhead wear is essentially the dynamic interaction between the cutterhead and the rock. Based on the principles of metal tribology, wear is typically categorized into adhesive wear (when the cutterhead slides against the rock, localized metal adhesion occurs at the cutterhead-rock contact surface; as the cutterhead moves, material is removed from the cutterhead surface during relative sliding, and the detached metal fragments further wear the cutterhead surface), abrasive wear (during rock breaking, hard rock fragments compress the cutterhead surface or perform micro-cutting along the cutterhead surface, causing material loss), and fatigue wear (under alternating contact compressive stress, material loss occurs on the cutterhead surface). In actual operation, several wear forms usually occur simultaneously. Currently, coatings are often used to improve wear resistance, but the wear resistance and corrosion resistance of the coatings used at present still need to be improved. Summary of the Invention

[0003] To address the aforementioned problems, this application proposes a composite coating for the cutterhead surface of a tunnel boring machine (TBM), comprising the following raw materials in parts by weight: WC: 10-25 parts; TiC: 5-20 parts; nickel-chromium alloy: 60-80 parts; the composite coating is obtained from the above raw materials through laser cladding. Based on the advantages of laser cladding, this application utilizes WC, TiC, and nickel-chromium alloy to obtain a composite coating for the TBM cutterhead surface that meets the requirements for hardness and wear resistance.

[0004] Preferably, a high-energy laser is used to heat the working surface of the hobbing cutter to form a high-temperature molten pool. Then, the raw material is introduced into the high-temperature molten pool on the surface of the hobbing cutter to melt and then rapidly cooled to form a cladding layer. The number of laser-coated layers is not less than five.

[0005] Preferably, the process also includes a preliminary cleaning of the hobbing cutter surface. After the preliminary cleaning, WO3 is applied to the hobbing cutter surface using laser cladding, with no more than two layers of laser coating. This application ensures the stability of the coating after the composite coating is applied to the hobbing cutter surface by independently applying WO3 to form a connecting surface.

[0006] Preferably, the laser power for laser heating is 1200W, the scanning speed is 500mm / min, the spot diameter is 2mm, the laser absorption rate is 25%, and the initial temperature is 24℃.

[0007] Preferably, the laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0008] Preferably, the raw materials are introduced by using a dual-pipe four-way blower coaxially feeding method.

[0009] Preferably, the particle size of WC and TiC is 15-45 μm; the particle size of the nickel-chromium alloy is 45-105 μm.

[0010] Preferably, the nickel-chromium alloy comprises the following elements in parts by mass:

[0011] Ni: 70-72 parts; Cr: 12-16 parts; Si: 4-5 parts; Fe: 3.5-5 parts; B: 2.8-3.2 parts; C: 0.75 parts.

[0012] Preferably, the total amount of WC and TiC accounts for 30-40 wt% of the total mass of the raw materials. This application uses TiC, WC, and nickel-chromium powder as laser cladding powder materials. Since the WC content in TiC-based cermet powder should not exceed 40 wt%, excessive WC content will lead to reduced hardness and poor wear resistance of the composite coating, while insufficient content will prevent the formation of a concentration gradient of W in the molten pool, which is detrimental to the formation of the core-shell structure. Therefore, this experiment controls the wear resistance effect by controlling the total amount of WC and TiC.

[0013] Preferably, WC powder, TiC powder, and nickel-chromium alloy powder are mixed and placed in a ball mill, with argon gas added as a protective gas and steel balls used as grinding media. The mixture is ball-milled at a speed of not less than 240 r / min for not less than 8 hours to achieve uniform mixing.

[0014] This application can bring the following beneficial effects:

[0015] 1. Based on the advantages of laser cladding, this application utilizes WC, TiC, and nickel-chromium alloys to obtain a composite coating on the surface of the tunnel boring machine cutter that meets the requirements for hardness and wear resistance.

[0016] 2. This application uses independently set WO3 to form a connecting surface on the hobbing surface, ensuring the stability of the coating after the composite coating is applied to the hobbing surface.

[0017] 3. This application uses TiC, WC, and nickel-chromium powder as laser cladding powder materials. Since the WC content in TiC-based cermet powder should not exceed 40wt%, too much WC will reduce the hardness of the composite coating and worsen its wear resistance, while too little WC will prevent the W concentration gradient in the molten pool from forming, which is not conducive to the formation of the core-shell structure. Therefore, this experiment controls the wear resistance effect by controlling the total amount of WC and TiC. Detailed Implementation

[0018] To clearly illustrate the technical features of this solution, the following detailed description of specific implementation methods will be provided.

[0019] This application actually discloses a composite coating for the cutterhead surface of a tunnel boring machine, comprising the following raw materials in parts by weight: WC: 10-25 parts; TiC: 5-20 parts; nickel-chromium alloy: 60-80 parts; the composite coating is obtained from the above raw materials by laser cladding.

[0020] Specifically, a high-energy laser is used to heat the working surface of the hobbing cutter to form a high-temperature molten pool. Then, the raw material is introduced into the high-temperature molten pool on the surface of the hobbing cutter to melt and then rapidly cooled to form a cladding layer. The number of laser-coated layers is no less than five.

[0021] Before processing, a preliminary cleaning pretreatment is required. Generally, this involves grinding and polishing first, followed by ultrasonic cleaning with anhydrous ethanol. It also includes a preliminary cleaning process for the hobbing surface. After the preliminary cleaning, WO3 is coated onto the hobbing surface using laser cladding. The number of laser coating layers should not exceed two.

[0022] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0023] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0024] The raw materials are introduced by using a dual-pipe four-way blower to coaxially feed the powder.

[0025] The particle size of WC and TiC is 15-45 μm; the particle size of the nickel-chromium alloy is 45-105 μm.

[0026] The nickel-chromium alloy comprises the following elements in parts by mass:

[0027] Ni: 70-72 parts; Cr: 12-16 parts; Si: 4-5 parts; Fe: 3.5-5 parts; B: 2.8-3.2 parts; C: 0.75 parts.

[0028] The total amount of WC and TiC accounts for 30-40 wt% of the total mass of the raw materials.

[0029] It also includes a pre-mixing process, in which WC powder, TiC powder, and nickel-chromium alloy powder are mixed and placed into a ball mill, argon is added as a protective gas, steel balls are used as grinding media, and the mixture is ball-milled at a speed of not less than 240 r / min for not less than 8 hours to achieve uniform mixing.

[0030] Specifically, the following steps are required:

[0031] S1. Premixing of composite coating raw materials

[0032] Mix 10-25 parts of WC powder, 5-20 parts of TiC powder, and 60-80 parts of nickel-chromium alloy powder and put them into a ball mill. Add argon gas as a protective gas and steel balls as grinding media. Ball mill the mixture at a speed of not less than 240 r / min for not less than 8 hours to achieve uniform mixing.

[0033] The particle size of WC and TiC is 15-45 μm; the particle size of the nickel-chromium alloy is 45-105 μm.

[0034] The nickel-chromium alloy comprises the following elements in parts by mass:

[0035] Ni: 70-72 parts; Cr: 12-16 parts; Si: 4-5 parts; Fe: 3.5-5 parts; B: 2.8-3.2 parts; C: 0.75 parts.

[0036] The total amount of WC and TiC accounts for 30-40 wt% of the total mass of the raw materials.

[0037] S2. Steel surface cleaning treatment

[0038] For H13 steel, the surface is first ground and polished, and then ultrasonically cleaned with anhydrous ethanol.

[0039] S3. Set WO3 layer

[0040] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0041] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0042] A high-energy laser is used to heat the working surface of the hobbing cutter to form a high-temperature molten pool. Then, the WO3 layer is introduced into the high-temperature molten pool on the surface of the hobbing cutter and melted. After rapid cooling, a cladding layer is formed. The number of laser-coated layers does not exceed two.

[0043] S4 features a composite coating.

[0044] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0045] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0046] A high-energy laser is used to heat the working surface of the hobbing cutter to form a high-temperature molten pool. Then, the raw material of the composite coating is introduced into the high-temperature molten pool on the surface of the hobbing cutter to melt and then rapidly cooled to form a cladding layer. The number of laser coating layers is no less than five.

[0047] Specific examples are shown below:

[0048] Example 1:

[0049] S101. Premixing of composite coating raw materials

[0050] 10 parts WC powder, 20 parts TiC powder, and 60 parts nickel-chromium alloy powder were mixed and placed in a ball mill. Argon gas was added as a protective gas, and steel balls were used as grinding media. The mixture was ball-milled at 240 r / min for 8 hours to achieve uniform mixing.

[0051] The particle size of WC and TiC is 15-45 μm; the particle size of the nickel-chromium alloy is 45-105 μm.

[0052] The nickel-chromium alloy comprises the following elements in parts by mass:

[0053] Ni: 71 parts; Cr: 15 parts; Si: 4.5 parts; Fe: 4.5 parts; B: 4.25 parts; C: 0.75 parts;

[0054] That is, Ni: 71wt%; Cr: 15wt%; Si: 4.5wt%; Fe: 4.5wt%; B: 4.25wt%; C: 0.75wt%.

[0055] S102. Steel surface cleaning treatment

[0056] For H13 steel, the surface is first ground and polished, and then ultrasonically cleaned with anhydrous ethanol.

[0057] S103. Set WO3 layer

[0058] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0059] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0060] A high-temperature molten pool is formed by laser heating on the working surface of the hobbing cutter using a high-energy laser. Then, the WO3 layer is introduced into the high-temperature molten pool on the surface of the hobbing cutter and melted. After rapid cooling, a cladding layer is formed. The number of laser coating layers is two.

[0061] S104 features a composite coating.

[0062] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0063] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0064] A high-energy laser is used to heat the WO3-coated hobbing surface to form a high-temperature molten pool. Then, the raw material for the composite coating is introduced into the high-temperature molten pool on the surface of the hobbing surface, melted, and then rapidly cooled to form a cladding layer. The laser coating consists of five layers.

[0065] A reciprocating sliding friction and wear test was conducted using an RTECMFT-3000 friction and wear testing machine to measure the friction coefficients of the cladding layer and the base steel. The test parameters were: a loading force of 50 N, a displacement stroke of 10 mm, a test time of 3600 s, and a GCr15 steel ball as the grinding workpiece. After the test, the wear volume was measured and calculated using a white light interferometer. In this experiment, the wear volume V was determined using a white light interferometer 3D optical profilometer. White light emits light of a specific wavelength through a specific instrument. Then, under the action of a beam splitter, the light of the specific wavelength is split into two beams. One beam is projected onto the sample, and the other beam is projected onto the surface of a reference mirror. These two beams are reflected and then processed again by the instrument before being combined into one beam. Finally, the imaging system forms two superimposed images on the photosensitive surface of the CCD. Under the action of mutual interference, the two beams form alternating bright and dark interference fringes on the photosensitive surface of the CCD. Since the sample surface is not smooth, the degree of roughness affects the optical path difference between the two beams, which in turn affects the brightness of the interference fringes. Based on the brightness of the interference fringes, the relative height of the sample surface can be determined, ultimately generating a 3D contour map of the wear track. This map characterizes the variation of the cladding layer wear track in the depth direction and is used to calculate the wear volume of the cladding layer, which is 2.120 mm. 2 .

[0066] Example 2:

[0067] S201. Premixing of composite coating raw materials

[0068] 25 parts WC powder, 10 parts TiC powder, and 80 parts nickel-chromium alloy powder were mixed and placed in a ball mill. Argon gas was added as a protective gas, and steel balls were used as grinding media. The mixture was ball-milled at 240 r / min for 8 hours to achieve uniform mixing.

[0069] The particle size of WC and TiC is 15-45 μm; the particle size of the nickel-chromium alloy is 45-105 μm.

[0070] The nickel-chromium alloy comprises the following elements in parts by mass:

[0071] Ni: 71 parts; Cr: 15 parts; Si: 4.5 parts; Fe: 4.5 parts; B: 4.25 parts; C: 0.75 parts.

[0072] That is, Ni: 71wt%; Cr: 15wt%; Si: 4.5wt%; Fe: 4.5wt%; B: 4.25wt%; C: 0.75wt%.

[0073] S202. Steel Surface Cleaning Treatment

[0074] For H13 steel, the surface is first ground and polished, and then ultrasonically cleaned with anhydrous ethanol.

[0075] S203. Set WO3 layer

[0076] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0077] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0078] A high-temperature molten pool is formed by laser heating on the working surface of the hobbing cutter using a high-energy laser. Then, the WO3 layer is introduced into the high-temperature molten pool on the surface of the hobbing cutter and melted. After rapid cooling, a cladding layer is formed. The number of laser coating layers is two.

[0079] S204 features a composite coating.

[0080] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0081] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0082] A high-energy laser is used to heat the WO3-coated hobbing surface to form a high-temperature molten pool. Then, the raw material for the composite coating is introduced into the high-temperature molten pool on the surface of the hobbing surface, melted, and then rapidly cooled to form a cladding layer. The laser coating consists of five layers.

[0083] A reciprocating sliding friction and wear test was conducted using an RTECMFT-3000 friction and wear testing machine to measure the friction coefficients of the cladding layer and the base steel. The test parameters were: a loading force of 50 N, a displacement stroke of 10 mm, a test time of 3600 s, and a GCr15 steel ball as the grinding workpiece. After the test, the wear volume was measured and calculated using a white light interferometer. In this experiment, the wear volume V was determined using a white light interferometer 3D optical profilometer. White light emits light of a specific wavelength through a specific instrument. Then, under the action of a beam splitter, the light of the specific wavelength is split into two beams. One beam is projected onto the sample, and the other beam is projected onto the surface of a reference mirror. These two beams are reflected and then processed again by the instrument before being combined into one beam. Finally, the imaging system forms two superimposed images on the photosensitive surface of the CCD. Under the action of mutual interference, the two beams form alternating bright and dark interference fringes on the photosensitive surface of the CCD. Since the sample surface is not smooth, the degree of roughness affects the optical path difference between the two beams, which in turn affects the brightness of the interference fringes. Based on the brightness of the interference fringes, the relative height of the measured sample surface can be determined, ultimately generating a 3D contour map of the wear track. This map characterizes the variation of the cladding layer wear track in the depth direction and is used to calculate the wear volume of the cladding layer, which is 1.781 mm. 2 .

[0084] To determine the effectiveness of the above scheme, the following comparative example was performed:

[0085] Comparative Example 1:

[0086] S301. Premixing of composite coating raw materials

[0087] 25 parts WC powder, 10 parts TiC powder, and 80 parts nickel-chromium alloy powder were mixed and placed in a ball mill. Argon gas was added as a protective gas, and steel balls were used as grinding media. The mixture was ball-milled at 240 r / min for 8 hours to achieve uniform mixing.

[0088] The particle size of WC and TiC is 15-45 μm; the particle size of the nickel-chromium alloy is 45-105 μm.

[0089] The nickel-chromium alloy comprises the following elements in parts by mass:

[0090] Ni: 71 parts; Cr: 15 parts; Si: 4.5 parts; Fe: 4.5 parts; B: 4.25 parts; C: 0.75 parts.

[0091] That is, Ni: 71wt%; Cr: 15wt%; Si: 4.5wt%; Fe: 4.5wt%; B: 4.25wt%; C: 0.75wt%.

[0092] S302. Cleaning treatment of steel surfaces

[0093] For H13 steel, the surface is first ground and polished, and then ultrasonically cleaned with anhydrous ethanol.

[0094] S303 features a composite coating.

[0095] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0096] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0097] A high-energy laser is used to heat the working surface of the hobbing cutter to form a high-temperature molten pool. Then, the raw material of the composite coating is introduced into the high-temperature molten pool on the surface of the hobbing cutter to melt and then rapidly cooled to form a cladding layer. The number of laser coating layers is five.

[0098] A reciprocating sliding friction and wear test was conducted using an RTECMFT-3000 friction and wear testing machine to measure the friction coefficients of the cladding layer and the base steel. The test parameters were: a loading force of 50 N, a displacement stroke of 10 mm, a test time of 3600 s, and a GCr15 steel ball as the grinding workpiece. After the test, the wear volume was measured and calculated using a white light interferometer. In this experiment, the wear volume V was determined using a white light interferometer 3D optical profilometer. White light emits light of a specific wavelength through a specific instrument. Then, under the action of a beam splitter, the light of the specific wavelength is split into two beams. One beam is projected onto the sample, and the other beam is projected onto the surface of a reference mirror. These two beams are reflected and then processed again by the instrument before being combined into one beam. Finally, the imaging system forms two superimposed images on the photosensitive surface of the CCD. Under the action of mutual interference, the two beams form alternating bright and dark interference fringes on the photosensitive surface of the CCD. Since the sample surface is not smooth, the degree of roughness affects the optical path difference between the two beams, which in turn affects the brightness of the interference fringes. Based on the brightness of the interference fringes, the relative height of the sample surface can be determined, ultimately generating a 3D contour map of the wear track. This map characterizes the variation of the cladding layer wear track in the depth direction and is used to calculate the wear volume of the cladding layer, which is 5.845 mm. 2 .

[0099] Comparative Example 2:

[0100] S401. Premixing of composite coating raw materials

[0101] 10 parts of TiC powder and 80 parts of nickel-chromium alloy powder were mixed and placed in a ball mill. Argon gas was added as a protective gas and steel balls were used as grinding media. The mixture was ball-milled at 240 r / min for 8 hours to achieve uniform mixing.

[0102] The TiC has a particle size of 15-45 μm; the nickel-chromium alloy has a particle size of 45-105 μm.

[0103] The nickel-chromium alloy comprises the following elements in parts by mass:

[0104] Ni: 71 parts; Cr: 15 parts; Si: 4.5 parts; Fe: 4.5 parts; B: 4.25 parts; C: 0.75 parts.

[0105] That is, Ni: 71wt%; Cr: 15wt%; Si: 4.5wt%; Fe: 4.5wt%; B: 4.25wt%; C: 0.75wt%.

[0106] S402. Steel Surface Cleaning Treatment

[0107] For H13 steel, the surface is first ground and polished, and then ultrasonically cleaned with anhydrous ethanol.

[0108] S403. Set WO3 layer

[0109] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0110] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0111] A high-temperature molten pool is formed by laser heating on the working surface of the hobbing cutter using a high-energy laser. Then, the WO3 layer is introduced into the high-temperature molten pool on the surface of the hobbing cutter and melted. After rapid cooling, a cladding layer is formed. The number of laser coating layers is two.

[0112] S404 features a composite coating.

[0113] For heating, a laser with a power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃ is used.

[0114] The laser is a C2000X fiber laser with a maximum power of 2000W, a wavelength of 1.08μm, a fiber diameter of 500μm, and a spot diameter of 2mm.

[0115] A high-energy laser is used to heat the WO3-coated hobbing surface to form a high-temperature molten pool. Then, the raw material for the composite coating is introduced into the high-temperature molten pool on the surface of the hobbing surface, melted, and then rapidly cooled to form a cladding layer. The laser coating consists of five layers.

[0116] A reciprocating sliding friction and wear test was conducted using an RTECMFT-3000 friction and wear testing machine to measure the friction coefficients of the cladding layer and the base steel. The test parameters were: a loading force of 50 N, a displacement stroke of 10 mm, a test time of 3600 s, and a GCr15 steel ball as the grinding workpiece. After the test, the wear volume was measured and calculated using a white light interferometer. In this experiment, the wear volume V was determined using a white light interferometer 3D optical profilometer. White light emits light of a specific wavelength through a specific instrument. Then, under the action of a beam splitter, the light of the specific wavelength is split into two beams. One beam is projected onto the sample, and the other beam is projected onto the surface of a reference mirror. These two beams are reflected and then processed again by the instrument before being combined into one beam. Finally, the imaging system forms two superimposed images on the photosensitive surface of the CCD. Under the action of mutual interference, the two beams form alternating bright and dark interference fringes on the photosensitive surface of the CCD. Since the sample surface is not smooth, the degree of roughness affects the optical path difference between the two beams, which in turn affects the brightness of the interference fringes. Based on the brightness of the interference fringes, the relative height of the measured sample surface can be determined, ultimately generating a 3D contour map of the wear track. This map characterizes the variation of the cladding layer wear track in the depth direction and is used to calculate the wear volume of the cladding layer, which is 4.142 mm. 2 .

[0117] The above are merely embodiments of this application and are not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.

Claims

1. A composite coating for the cutterhead surface of a tunnel boring machine, characterized in that: The raw materials include the following parts by weight: WC: 10-25 parts; TiC: 5-20 parts; nickel-chromium alloy: 60-80 parts; the composite coating is obtained from the above raw materials by laser cladding. The composite coating is prepared according to the following steps: S1. Premixing of composite coating raw materials Mix 10-25 parts of WC powder, 5-20 parts of TiC powder, and 60-80 parts of nickel-chromium alloy powder and put them into a ball mill. Add argon gas as a protective gas and steel balls as grinding media. Ball mill the mixture at a speed of not less than 240 r / min for not less than 8 hours to achieve uniform mixing. The particle size of WC and TiC is 15-45 μm; the particle size of the nickel-chromium alloy is 45-105 μm. The nickel-chromium alloy comprises the following elements in parts by mass: Ni: 71 parts; Cr: 15 parts; Si: 4.5 parts; Fe: 4.5 parts; B: 4.25 parts; C: 0.75 parts; that is, Ni: 71 wt%; Cr: 15 wt%; Si: 4.5 wt%; Fe: 4.5 wt%; B: 4.25 wt%; C: 0.75 wt% The total mass ratio of WC and TiC to the total raw materials is 30-40 wt%. S2. Steel surface cleaning treatment For H13 steel, the surface is first ground and polished, and then ultrasonically cleaned with anhydrous ethanol. S3. Set WO3 layer A high-temperature molten pool is formed by laser heating on the working surface of the hobbing cutter using a high-energy laser. Then, the WO3 layer is introduced into the high-temperature molten pool on the surface of the hobbing cutter and melted. After rapid cooling, it forms a cladding layer. The number of laser-coated layers does not exceed two. The laser heating system has a laser power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃. S4 features a composite coating. A high-temperature molten pool is formed by laser heating of the working surface of the hob cutter using a high-energy laser. Then, the raw material of the composite coating is introduced into the high-temperature molten pool on the surface of the hob cutter and melted and then rapidly cooled to form a cladding layer. The number of laser coating layers is no less than five. The laser heating system has a laser power of 1200W, a scanning speed of 500mm / min, a spot diameter of 2mm, a laser absorption rate of 25%, and an initial temperature of 24℃.

Citation Information

Patent Citations

  • Method for preparing self-sharpening tool based on tool cutting edge surface laser cladding treatment

    CN110218998A